Sistem Pengukuran Kinerja Supply Chain Management Pada Proyek Konstruksi - Demi Ramadian; Elita Amrina (Jurnal Optimasi Sistem Industri, 2019)
Construction project implementation process is often found inefficiency and problems at every stage of the construction process. Inefficiencies are caused because construction projects have high levels of fragmentation. The high level of fragmentation cannot be separated from the complexity and many work items on construction projects. To reduce the problem of inefficiencies in the implementation of construction projects required good supply chain management or better known as supply chain management (SCM) on construction projects. Therefore it is necessary to study the management of SCM in the construction project to reduce the inefficiency that occurred. SCM management of construction projects is done by designing SCM performance measurement systems in construction projects. This performance measurement system produces indicators that are combined with the Supply Chain Operation Reference (SCOR) method. So it helps in performing SCM performance measurement on construction projects. From the design results, obtained 14 SCM performance indicators on construction projects. The performance indicators are then used to perform SCM performance measurement of cement plant construction projects. From the measurement results obtained SCM performance value of 41 from a scale of 100. This shows the performance of SCM on construction projects for the construction of the cement plant is at a marginal level.